FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MAKANAN DAN MINUMAN - Sansoethan, Dithya Kusuma; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test both simultaneously and partially the influence of profitability, asset structure, asset growth, firm size, and liquidity to the capital. The samples are 11 food and beverages companies which are listed in Indonesia Stock Exchange in 2010-2014 periods and these companies have been selected by using purposive sampling. The result of the research shows that the regression models of this research have met the requirement that there are no symptoms of i.e.: heteroscedasticity, multicolinearity, and correlation and the data has been normally distributed. The result of the research shows that simultaneously profitability, asset structure, asset growth, firm size, and liquidity have significant influence to the capital structure, and the magnitude of the influence is 41%. Meanwhile, the result of partial research shows that from these five variables i.e.: profitability, asset structure, asset growth, firm size, and liquidity, there are two variables which have significant influence to the capital structure i.e.: asset structure and liquidity whereas profitability, asset growth, and firm size do not have any significant influence to the capital structure.Keywords: Profitability, Asset, Firm Size, Liquidity, Capital Structure